Decolonizing feminism: Challenging connections between settler colonialism and heteropatriarchy - Arvin, Maile; Tuck, Eve; Morrill, Angie (Feminist Formations, 2013)
The article explores two intertwined ideas: that the United States is a settler colonial nation-state and that settler colonialism has been and continues to be a gendered process. The article engages Native feminist theories to excavate the deep connections between settler colonialism and heteropatriarchy, highlighting five central challenges that Native feminist theories pose to gender and women's studies. From problematizing settler colonialism and its intersections to questioning academic participation in Indigenous dispossession, responding to these challenges requires a significant departure from how gender and women's studies is regularly understood and taught. Too often, the consideration of Indigenous peoples remains rooted in understanding colonialism as an historical point in time away from which our society has progressed. Centering settler colonialism within gender and women's studies instead exposes the still-existing structure of settler colonialism and its powerful effects on Indigenous peoples and settlers. Taking as its audience practitioners of both "whitestream" and other feminisms and writing in conversation with a long history of Native feminist theorizing, the article offers critical suggestions for the meaningful engagement of Native feminisms. Overall, it aims to persuade readers that attending to the links between heteropatriarchy and settler colonialism is intellectually and politically imperative for all peoples living within settler colonial contexts.
https://www.feministformations.org
Keywords: OFDIG; amériques; approches et analyses; colonialisme; féminisme autochtone; féminisme décolonial; intersectionnalité; militance; patriarcat; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Ethical waters: Reflections on the healing walk in the tar sands - Wong, Rita (Feminist Review, 2013)
Keywords: activisme; amériques; approches et analyses; autochtones; canada; cours; fem1000; féminisme autochtone; guérison; militance; premier cycle; ressource en ligne; régions géographiques; santé; thématiques